Dads make a difference: an exploratory study of paternal support for breastfeeding in Perth, Western Australia - Tohotoa, Jenny; Maycock, Bruce; Hauck, Yvonne; Howat, Peter; Burns, Sharyn; Binns, Colin (BioMed Central, 2009)
Background: The ability to breastfeed and continue the practice requires dedication,commitment, persistence and support. Mothers often need to overcome many obstacles tosuccessfully breastfeed their babies and maintain their balance of home, family and workcommitments. Evidence suggests that fathers want to be involved and be part of the parenthoodprocess, including infant feeding. The role transition from couple to family poses challenges to bothparents. Sharing the experience of childbirth and supporting each other in the subsequent infantfeeding practices is one of those challenges.Methods: A qualitative exploratory design was chosen to identify parents' perceptions of whatconstitutes support for breastfeeding, particularly focusing upon paternal support. Focus groupswere conducted with mothers and a focus group, interviews and an online survey were developedfor fathers. Thematic analysis was used to identify the main themes.Results: From a total of 76 participants, the major theme emerging from mothers' data identifiedthat "Dads do make a difference". Three sub-themes included: Anticipating needs and getting thejob done; Encouragement to do your best; and Paternal determination and commitment, associatedwith effective partner support. "Wanting to be involved" was identified from fathers' data as themajor theme around their needs. Three sub-themes included: Wanting more information; Learningthe role; and Being an advocate.Conclusion: Sharing the experience of childbirth and supporting each other in the subsequentinfant feeding practices was perceived as the best outcome for the majority of new mothers andfathers. Paternal emotional, practical and physical supports were identified as important factors topromote successful breastfeeding and to enrich the experience for the mother and subsequentlythe father.